How to deal with difficult people : smart tactics for overcoming the problem people in your life - Hasson, Gill (Capstone, 2015)
"Don't let problem people get you down, get in your way or get on your nerves!Some people are annoying. That's just a fact. Some people are demanding, difficult, unreasonable, awkward and infuriating. It's exhausting and frustrating to battle away with these people, desperately trying to get what you need as they make life difficult. Arrggghhh. It's time we stopped the agonizing and got these people out of our way. That's exactly what How to Deal With Difficult People can help us do. With frank discussion and clever, practical advice, bestselling author Gill Hasson, shares simple moves that make these people less of a problem. It's not about 'understanding' these people and trying to help them change - Gill's not suggesting you can help these people become glorious rays of sunshine - it's about getting them out of your way so they don't hold you back. How to get around these obstacles and reduce your own stress as a result. You'll learn how to control your reactions, choose your battles, and calmly navigate emotionally charged situations. How to deal with difficult people will help you: Learn ways to confidently stand up to others Learn how to resist the urge to lash out and attack back Develop strategies to remain calm Know when to choose your battles Know when to cut your losses and walk away You're under enough stress already - why should someone else's bad attitude add to that burden? You cannot make that person less difficult, and often, you can't just cut them out of your life. But you can stop allowing that person to ruin your day. How to Deal With Difficult People shows you how, with practical tools and expert guidance"--